Arabidopsis E2Fc is required for the DNA damage response under UV-B radiation epistatically over the microRNA396 and independently of E2Fe - Gomez, Maria Sol (2019)
UV-B radiation inhibits plant growth, and this inhibition is, to a certain extent, regulated by miR396-mediated repression of Growth Regulating Transcription factors (GRFs). Moreover, E2Fe transcription factor also modulates Arabidopsis leaf growth. Here, we provide evidence that, at UV-B intensities that induce DNA damage, E2Fc participates in the inhibition of cell proliferation. We demonstrate that E2Fc-deficient plants show a lower inhibition of leaf size under UV-B conditions that damage DNA, decreased cell death after exposure and altered SOG1 and ATR expression. Interestingly, the previously reported participation of E2Fe in UV-B responses, which is a transcriptional target of E2Fc, is independent and different from that described for E2Fc. Conversely, we here demonstrate that E2Fc has an epistatic role over the miR396 pathway under UV-B conditions. Finally, we show that inhibition of cell proliferation by UV-B is independent of the regulation of class II TCP transcription factors. Together, our results demonstrate that E2Fc is required for miR396 activity on cell proliferation under UV-B, and that its role is independent of E2Fe, probably modulating DNA damage responses through the regulation of SOG1 and ATR transcript levels.